Evaluating South Asia’s Pandemic Preparedness - Chathuni Pabasara; Ravindri Paranagama (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
The COVID-19 pandemic has underscored the need for pandemics to be recognized as serious and imminent threats to national and economic security and henceforth, the need to elevate pandemic preparedness as a critical component of public health infrastructure. Despite the lack of robust pandemic preparedness plans, South Asian countries were able to implement proactive lockdown measures to contain the spread of the virus during the early stages of COVID-19. However, public health systems in the region were soon overwhelmed by the drawn-out pandemic and surges in the number of cases, due to inadequate national public health emergency plans, limited public health infrastructure and human resources. The lack of sufficient resource allocation into preparedness plans and surveillance, exacerbated by the region’s socio-economic vulnerabilities, leaves South Asia exposed to future pandemics. While the success of strategies has been uneven across the Southeast Asian region; pandemic preparedness strategies shaped by lessons learned in managing disease outbreaks in the past, have facilitated the sharing of information, expertise and technical support through regional mechanisms. Such tools have been identified as critical to developing policy responses during infectious disease outbreaks. As zoonotic diseases are impossible to eliminate due to their animal origins, pandemics are an inevitable threat. Therefore, South Asia can address the gaps and weaknesses in their existing national preparedness plans and apply Southeast Asia’s best practices to improve their national and regional detection and response systems; reforming and elevating South Asia’s pandemic preparedness.